2016
DOI: 10.1016/j.molmet.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ambient temperature promotes inflammation and initiates atherosclerosis in wild type C57BL/6 mice

Abstract: ObjectivesObesity and obesity-associated inflammation is central to a variety of end-organ sequelae including atherosclerosis, a leading cause of death worldwide. Although mouse models have provided important insights into the immunopathogenesis of various diseases, modeling atherosclerosis in mice has proven difficult. Specifically, wild-type (WT) mice are resistant to developing atherosclerosis, while commonly used genetically modified mouse models of atherosclerosis are poor mimics of human disease. The lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 42 publications
5
72
0
1
Order By: Relevance
“…This increase in atherogenesis was associated with inflammatory changes in and around the vessel wall, as evidenced by increased infiltration of vessel wall and perivascular fat by inflammatory macrophages and dendritic cells. A similar increase in lesion area was observed by Giles et al, who found that Apoe -/- mice housed at thermoneutrality had larger atherosclerotic lesions in their aortic roots 70 . These investigators also tested whether thermoneutral housing might induce atherogenesis in C57BL/6J mice, which are normally resistant to development of atherosclerosis.…”
Section: Inflammation and Metabolic Diseasessupporting
confidence: 84%
See 1 more Smart Citation
“…This increase in atherogenesis was associated with inflammatory changes in and around the vessel wall, as evidenced by increased infiltration of vessel wall and perivascular fat by inflammatory macrophages and dendritic cells. A similar increase in lesion area was observed by Giles et al, who found that Apoe -/- mice housed at thermoneutrality had larger atherosclerotic lesions in their aortic roots 70 . These investigators also tested whether thermoneutral housing might induce atherogenesis in C57BL/6J mice, which are normally resistant to development of atherosclerosis.…”
Section: Inflammation and Metabolic Diseasessupporting
confidence: 84%
“…Because thermoneutral housing accelerated the onset of metabolic inflammation during obesity 62 , two recent studies asked whether it might potentiate vascular inflammation and atherosclerosis 62,70 . Using the Apoe -/- mice, Tian et al found that thermoneutral housing enhanced the development of atherogenic lesions in the aortas of mice fed the western diet 62 .…”
Section: Inflammation and Metabolic Diseasesmentioning
confidence: 99%
“…Aortic sinus disease, which we quantified in the present study along with aortic disease at multiple time points, was not examined by Tian et al Giles et al failed to find a major shift in plasma cholesterol but nonetheless reported that enhanced atherosclerosis was worsened in Apoe −/− mice fed a high fat diet, but there was no disease change in Apoe −/− mice fed a chow diet. They then went on to report that, surprisingly, WT C57BL/6 mice developed modest, but measureable, atherosclerosis when fed a high fat diet and housed at thermoneutrality 54 . For unclear reasons as of yet, these two studies appear directly at odds with the conclusions from our work and that of Dong et al 21 .…”
Section: Discussionmentioning
confidence: 99%
“…TG quantification was performed as reported . Briefly, 200 μL of triglyceride reagent (Pointe Scientific) was added to 10 μL of serum in a 96‐well, clear, flat‐bottom plate (Costar).…”
Section: Methodsmentioning
confidence: 99%